Alur Penegakan Hukum dalam Kasus Pidana Berdasarkan Tugas serta Fungsi dari Hakim dan Jaksa di Indonesia - Fa’iq Walid Abidin, Rijal; Iqbal Fadhlurrahman, Maulana (Adagium: Jurnal Ilmiah Hukum, 2025)
Law enforcement in Indonesia is a topic that is always interesting to discuss. This is because law enforcement in Indonesia is a complex process and involves various parties with tasks and functions that are interrelated with each other. In practice, the flow of law enforcement in Indonesia does not always run according to what it should be. This is because there is a mismatch between expectations and the reality of how the applicable legal system works, causing the binding force of the law and its transparency in law enforcement in Indonesia. This research uses a qualitative approach and descriptive-analytical method, which is normative type with data collection techniques in the form of literature studies and case studies of legal literature. It highlights the crucial role played by judges and prosecutors in ensuring justice and the sustainability of the legal process in Indonesia. The final result of the research on the flow of law enforcement in criminal cases begins with investigations conducted by police officers, which are then followed by the role of prosecutors in prosecution. The synergy between prosecutors and judges in the criminal justice process is crucial to creating an effective and fair legal system and requires close and professional cooperation between these two institutions to maintain the integrity of the justice system, protect individual rights, and create social justice in society.